Ассоциация полиморфизмов гена СОМТ с болезнью Паркинсона; Бюллетень сибирской медицины; Т. 16, № 3 - Иванова С. А. Светлана Александровна; Алифирова В. М. Валентина Михайловна; Жукова И. А. Ирина Александровна; Тигунцев В. В. Владимир Владимирович; Пожидаев И. В. Иван Вячеславович; Османова Д. З. Диана Закировна; Федоренко О. Ю. Ольга Юрьевна; Фрейдин М. Б. Максим Борисович; Миронова Ю. С. Юлия Сергеевна; Жукова Н. Г. Наталья Григорьевна; Бохан Н. А. Николай Александрович; Лунен А. Дж. М. (2017, 2017)
Заглавие с экрана